Validity and Reliability of the Indonesian Version of Nordic Occupational Skin Questionnaire 2002 (NOSQ-2002) - Paramita, Listya; Waskito, Fajar; Prawiratama, Dikky; Indrastuti, Niken; Rayinda, Tuntas; Febriana, Sri Awalia (UI Scholars Hub, 2025)
Background: Epidemiological data on occupational hand eczema in Indonesia is still limited, partly because there are no valid and reliable instruments in the Indonesian language as a means of survey. This study aims to translate the Nordic Occupational Skin Questionnaire 2002 (NOSQ-2002) into the Indonesian language and assess the validity and reliability of the Indonesian NOSQ-2002 as an instrument for epidemiological surveys and screening of occupational hand eczema. Methods: The original English version of NOSQ-2002 was translated into the Indonesian language following the standard procedure of translation. The Indonesian NOSQ-2002 version, which had been collectively approved, was subsequently completed by a group of 194 textile employees from PT. Panca Persada Mulia-PANDATEX in Magelang, Central Java, Indonesia. Validity was assessed using Pearson correlation for each question with the total score. Reliability was evaluated using Cronbach's alpha values. The sensitivity and specificity of the Indonesian NOSQ-2002 screening were determined by comparing results with those of examination by the examining physician as the gold standard. Results: Pearson correlation values for each question range from 0.252 to 0.905, all surpassing the r table value, indicating questions in NOSQ-2002 are valid. Reliability NOSQ-2002 rated good (reliable), with a Cronbach's alpha of 0.933. The Indonesian NOSQ-2002 version demonstrates a sensitivity of 93.3% and specificity of 98.8% for screening occupational hand eczema. Conclusion: The Indonesian version of NOSQ-2002 is a valid and reliable instrument for use in epidemiological surveys and screening of occupational hand eczema.